1974
DOI: 10.1037/h0036662
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of locus of control and type of performance feedback: Considerations of external validity.

Abstract: Two studies were carried out to establish the generality of Baron and Ganz's finding of a significant Locus of Control X Type of Performance Feedback interaction. The superior performance of internals to externals under a condition of self-discovery of success (intrinsic feedback), as opposed to the superior performance of externals to internals when unverifiable verbal praise is used (extrinsic feedback), was found to occur for lower-class white as well as lower-class black subjects (Study 1), and for college… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…143). However, there are deviant findings, too, indicating that externals are receptive at least to cues of a social nature (Baron, Cowan, Ganz, & McDonald, 1974;Baron & Ganz, 1972;Fitz, 1971;Lefcourt, 1976).…”
Section: Purpose and Hypothesesmentioning
confidence: 99%
“…143). However, there are deviant findings, too, indicating that externals are receptive at least to cues of a social nature (Baron, Cowan, Ganz, & McDonald, 1974;Baron & Ganz, 1972;Fitz, 1971;Lefcourt, 1976).…”
Section: Purpose and Hypothesesmentioning
confidence: 99%
“…Finally, past studies have shown that, relative to externals (people with external control beliefs), internals (people with internal control beliefs) are more inclined to approach situations of unfavorable social comparison as opportunities to learn and grow (Baron, Cowan, Ganz, & McDonald, 1974;Ilgen, Fisher, & Taylor, 1979). Thus, we would expect internals to respect and strive for the accomplishments of others without necessarily undermining envied coworkers.…”
Section: Moderators Of Envy's Effectsmentioning
confidence: 99%
“…Employees high in self-efficacy also tend to be high performers at work and to persist in the face of setbacks (Gist & Mitchell, 1992;Judge & Bono, 2001;Stajkovic & Luthans, 1998). Employees with an internal locus of control also share this quality of persistence in the face of negative feedback (Baron et al, 1974;Ilgen et al, 1979). Qualities such as these provide foundations for a challenge orientation to overcome perceived inequity.…”
Section: Moderators Of Envy's Effectsmentioning
confidence: 99%
“…Unlike the other measures, the IAR also provides separate subscores for positive and negative outcomes. Thus, respondents can receive an overall score measuring degree of internality as well as scores on subscales measuring perceived internality for success (I +) and for failure (I-).Twenty-one of these 22 studies(Baron, Cowan, Ganz, and McDonald, 1974, is the exception) compared Black and White children on locus of control. Seven of the studies, or 33%, show unequivocally that Whites are more internal, six reveal no differences between the races, and seven show mixed results.…”
mentioning
confidence: 99%